2018
DOI: 10.3390/md16060194
|View full text |Cite
|
Sign up to set email alerts
|

Novel Natural Products from Extremophilic Fungi

Abstract: Extremophilic fungi have been found to develop unique defences to survive extremes of pressure, temperature, salinity, desiccation, and pH, leading to the biosynthesis of novel natural products with diverse biological activities. The present review focuses on new extremophilic fungal natural products published from 2005 to 2017, highlighting the chemical structures and their biological potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 98 publications
0
37
0
2
Order By: Relevance
“…It can also be anticipated that improvements in search and discovering pipelines will be promoted in no small measure by focusing heavily on novel culturable micro‐organisms with large genomes, as advocated by Baltz (, ). In this context, future bioprospecting campaigns should not only be focused on micro‐organisms like actinobacteria and fungi that are known to have a prosperity to synthesize antibiotics of therapeutic value (Bérdy ; Newman and Cragg ; Zhang et al ), but also on representatives of under‐explored micro‐organisms with genomes rich in NP‐BGCs, such as cyanobacteria, frankiae, ktedonobacteria and myxobacteria, representatives of all of these taxa are known to be attractive candidates for drug discovery programmes (Dixit and Suseela ; Micallef et al ; Baltz ; Nouioui et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be anticipated that improvements in search and discovering pipelines will be promoted in no small measure by focusing heavily on novel culturable micro‐organisms with large genomes, as advocated by Baltz (, ). In this context, future bioprospecting campaigns should not only be focused on micro‐organisms like actinobacteria and fungi that are known to have a prosperity to synthesize antibiotics of therapeutic value (Bérdy ; Newman and Cragg ; Zhang et al ), but also on representatives of under‐explored micro‐organisms with genomes rich in NP‐BGCs, such as cyanobacteria, frankiae, ktedonobacteria and myxobacteria, representatives of all of these taxa are known to be attractive candidates for drug discovery programmes (Dixit and Suseela ; Micallef et al ; Baltz ; Nouioui et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Penicillum spp. isolated from an abandoned open-pit containing acid-metal waste in Montana, USA were found to produce interesting, novel bioactive compounds (Zhang et al 2018), whereas algae from acid mine waste have been identified as Chlorella protothecoids var. acidicola and Euglena mutabolis (Johnson 2012).…”
Section: Eukaryotesmentioning
confidence: 99%
“…Breviones (96-99), isolated from the deepest sediment-derived fungus Penicillium sp. (5115 m depth), displayed diverse activities, such as cytotoxicity against HeLa, MCF-7, and A549 cells with IC 50 values of 7.44 to 32.5 µM, respectively, and growth inhibition of HIV-1 with EC 50 value of 14.7 µM against C8166 cells [22,38]. Compounds 100-110 showed antibiotic and inhibition activities against silkworm, while 20-nor-isopimarane diterpenoids, including aspewentins (114-118), asperethers (121-125), asperoloids (119-120), and compounds 130 and 131, showed cytotoxic activities [33,[39][40][41][42][43][44][45].…”
Section: Terpenoid Compoundsmentioning
confidence: 99%
“…compounds 47 and 48 were extracted from other genera and showed antimicrobial activity (MIC between 16 and 64 µg/mL against Escherichia coli, Aeromonas hydrophila, Micrococcus luteus, Staphylococcus aureus, Vibrio anguillarum, Vibrio harveyi, and Vibrio parahaemolyticus) and cytotoxic activity against human cervical carcinoma HeLa, respectively[22][23][24][25][26]. while compounds 47 and 48 were extracted from other genera and showed antimicrobial activity (MIC between 16 and 64 µ g/mL against Escherichia coli, Aeromonas hydrophila, Micrococcus luteus, Staphylococcus aureus, Vibrio anguillarum, Vibrio harveyi, and Vibrio parahaemolyticus) and cytotoxic activity against human cervical carcinoma HeLa, respectively[22][23][24][25][26].…”
mentioning
confidence: 99%
“…The UV/Vis spectrum showed absorption maxima at 590, 380, 285, and 245 nm. 13 C NMR shifts for compound 11 obtained from overlaid HMBC and 1 H- 13 C HSQC spectra exhibited one methyl signal at δ H 3.69 (CH 3 -23), fourteen aromatic methines grouped by 1 (Table 1). Additionally, fourteen quaternary carbon atoms were identified from 1 H- 13 C HSQC and 1 H- 13 C HMBC as well as 1 H- 13 C HSQC and a 2 Hz long range 1 H- 13 C HMBC spectra, including three carbonyls C-11, C-15, and C-24 (δ C 165.…”
Section: Compound Identificationmentioning
confidence: 99%